2012
DOI: 10.1063/1.3699370
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic properties of porous titania grown by oblique angle deposition

Abstract: High surface area nanorods of titanium dioxide were grown by oblique angle deposition on a transparent substrate to investigate their effectiveness as photocatalytic agents for the destruction of organic contaminants in air and water. Optical transmission measurements were made that allowed for an estimation of the porosity of the film (75%-78%). Comparing transmission measurements with those from a dense anatase film showed that the penetration depth for the light into the nanorod film was 2.5 times that in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A complete derivation of this can be found in previous work. 4,17,32 The reaction rate constant is lowest for the unannealed film and reaches its highest value after only 3 min of annealing whether in nitrogen or oxygen (not shown). Further annealing in nitrogen for a total of 10 min or 20 min lowers the rate slightly, possibly because surface diffusion lowers the surface area, but is counteracted by the growth of the anatase phase.…”
Section: Gas Phase Photocatalysismentioning
confidence: 94%
See 3 more Smart Citations
“…A complete derivation of this can be found in previous work. 4,17,32 The reaction rate constant is lowest for the unannealed film and reaches its highest value after only 3 min of annealing whether in nitrogen or oxygen (not shown). Further annealing in nitrogen for a total of 10 min or 20 min lowers the rate slightly, possibly because surface diffusion lowers the surface area, but is counteracted by the growth of the anatase phase.…”
Section: Gas Phase Photocatalysismentioning
confidence: 94%
“…28 Upon annealing between 450 C and 600 C, the film composition increases in anatase content, 29 which is preferable for photocatalysis. 4,28,30 However, there is still a considerable amount of amorphous material present. The as-deposited films are also oxygen deficient, as a consequence of the evaporation process.…”
Section: B Annealingmentioning
confidence: 99%
See 2 more Smart Citations
“…25,26 It has been found that the as grown TiO 2 lms or columns by physical vapor deposition method under room temperature were typically amorphous, 27,28 and annealing at a temperature ranging from 300 to 700 C in air caused the formation of single anatase crystalline phase, 29 and also annealing at 400 and 500 C under O 2 ow varied the porosity and oxygen defect. 30 However, the photoelectrochemical and photocatalytic properties were not been discussed.…”
mentioning
confidence: 99%